A “Third Wheel” Effect in Health Decision Making Involving Artificial Entities: A Psychological Perspective - Triberti, Stefano; Durosini, Ilaria; Pravettoni, Gabriella (Frontiers in Public Health, 2020)
In the near future, Artificial Intelligence (AI) is expected to participate more and more in decision making processes, in contexts ranging from healthcare to politics. For example, in the healthcare context, doctors will increasingly use AI and machine learning devices to improve precision in diagnosis and to identify therapy regimens. One hot topic regards the necessity for health professionals to adapt shared decision making with patients to include the contribution of AI into clinical practice, such as acting as mediators between the patient with his or her healthcare needs and the recommendations coming from artificial entities. In this scenario, a “third wheel” effect may intervene, potentially affecting the effectiveness of shared decision making in three different ways: first, clinical decisions could be delayed or paralyzed when AI’s recommendations are difficult to understand or to explain to patients; second, patients’ symptomatology and medical diagnosis could be misinterpreted when adapting them to AI’s classifications; third, there may be confusion about roles and responsibilities among the protagonists of the healthcare process (e.g., Who really has authority?). This contribution delineates such effect and tries to identify the impact of AI technology on the healthcare process, with a focus on future medical practice.